The Role Of Perceived Technology Support, Digital Self-Efficacy, and Perceived Employability In Remote Workers' Career Satisfaction - Siregar, Tika Rahma Yani; Syahrizal, Syahrizal (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Remote workers have faced a sudden shift to virtual work without flexibility and often with inadequate training. This situation increases the burden related to technology. This study investigates the impact of perceived technology support and digital self-efficacy on career satisfaction among employees, and the mediating effect of perceived employability. This quantitative research was conducted using a survey approach. The study involved 210 remote workers, and data collection was conducted using a questionnaire, and analyzed using SmartPLS 4.0. The findings showed that perceived technology support had a positive influence on career satisfaction, while digital self-efficacy had no impact on career satisfaction. Perceived employability plays a mediating role in the relationship between perceived technology support, digital self-efficacy, and career satisfaction. This study extends the existing literature by exploring career satisfaction in the remote workers in the tourism industry.